Enterococcus spp. resistant to vancomycin and its spread in infections in the hospital environment (Research, Society and Development, 2020)
Objective: Describe the main virulence factors associated with this pathogen, with an emphasis on E. faecium and E. faecalis, demonstrating the main resistance genes involved in the mentioned species, as well as reporting the form of dissemination of these in hospital settings. Methodology: This article was prepared through Literature Review, based on materials indexed in the databases: PubMed, SciELO and Google Scholar, published between the years 2010 to 2020. For selection, the criteria were applied in the following order: (a) exploratory reading; (b) selective reading, (c) selection of material in accordance with the research objectives. Results: 789 files were found, of which 38 were selected for this article. Conclusion: The adoption of practices by the Hospital Infection Control team is very important, contributing to improvements in the quality of health care, thus increasing the safety of the entire team of professionals and patients.